Before the sale rights to agricultural land - Kustovska, О.; Grinchuk, A. (Land Management, Cadastre and Land Monitoring, 2017)
One of the most important problems of the Ukrainian economy is the formation of a civilized land market. We have to admit that the process of formation of private ownership of land in Ukraine entered into a protracted and uncertain nature. Another introduction in Ukraine of the moratorium on sale of agricultural land due to the lack of resolution of many land issues and not sformovat market infrastructure. Because for the majority of producers of agricultural products the sale of lease rights is an innovation. On the sale of lease rights still they are almost not heard, and especially not used in practice, although the possibility of disposal of property rights, which is owned and leasehold, provided by norms of the Civil code of Ukraine.The issue of land bidding (auction) is relevant, because the law of Ukraine set the priority of this method of trading in the sale or lease of land.The auction is open and transparent way the exclusion of land resources of the territorial community, that is, eliminates the influence of corruption and receipt of funds in local budgets adds the ability to invest in the economy of human settlements and agriculture. Among the economic benefits to the development industry is not only improving the investment climate, replenishment of budgets of all levels and approaching the level of EU countries in matters of land. Holding of auctions is very attractive from the point of view of filling the local budget, the sale of land has its advantages, namely a quick and significant revenue.The lease right may be alienated in accordance with the current legislation of Ukraine and some legislative solution is not needed.The procedure of land auctions includes the following steps:1. The organizer of land sales (public authority or local authority) determines the list of land plots of state or municipal property and rights thereto, which are exposed at the land auction as separate lots.2. The decision of a public authority or local authority on the land auction.3. Drawing of lots for the land auction includes: creation, coordination and approval of the project land for allotment of land (in case of changing the target purpose of the land plot and in case the boundaries of the land are not established in kind (on ground); state registration of the land plot; state registration of property rights to land; the receipt of the statement of regulatory monetary evaluation of land plot in case of sale of land auction the right to lease it; an expert monetary valuation of land, except in cases of sales of land auction the right to lease it; the establishment of the starting price sale of land, which on the lands of state and communal ownership cannot be lower than expert monetary valuation of land; the establishment of a starting annual rent of the lands of state and communal ownership may not be less than the amount of rent;4. A contract between the organizer of land sales and land auction administrator (business entity, which is licensed to conduct land auctions) for the tendering.5. Publication in print media and on the official website announcement indicating the date of tendering and list of lots. The absence of a land market is a rejection of the economic methods of land redistribution and, as a consequence, the introduction of administrative, which is a deviation from the formation of a market economic system. In all countries with a market economy with a high level of industrial development of agriculture and agribusiness was primarily achieved through the active participation of the state in providing legal and financial stability. This eliminates the preconditions of naturalization of agricultural production, and also introduced the principle of - land to those who it works better.Keywords: land, auction, lease, land market, the organization bidding.